Implementation Of Strengthening Character Education To Build Student Interpersonal Intelligence At Tourism Collection - Cecep Tatang Wijaya; Hanafiah; R Supyan Sauri; Faiz Karim Fatkhullah (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Weak character education for students in Indonesia, one of which is due to learning activities that have not been formulated as a humanization process that is rooted in moral and religious values, the education system is still schooling focused on knowledge transfer, limited teachers in educating student character, and weak implementation character building. This study generally aims to describe and analyze the Implementation of Strengthening Character Education to Foster Interpersonal Intelligence in Tourism Higher Education Students. This study uses a qualitative approach with a case study method and data collection techniques through interviews, documentation and observation. The results of the study show that planning character education is more directed by being service oriented, when students are going to do a comparative study, pay attention to the directions from the tour guide. The organization is in accordance with the industry's curriculum needs, but for excellent service/character it has not been optimally implemented, so it still follows conventional rules. The implementation shows the discipline to apply part of the character set conveyed through excellent service, so that changes in students are not significant. Evaluation in particular for students only received a warning for disciplinary action. Deficiencies and negative events in the field are discussed by fellow lecturers or managerial parties. This is illustrated through increasing student discipline towards campus values ​​and rules which have an impact on achieving the institution's vision, namely to create quality and superior students in character and life skills.